The Importance of Interdisciplinary Research Training and Community Dissemination. Issue 5 (10th September 2015) - Gill, Simone V.; Vessali, Misha; Pratt, Jacob A.; Watts, Samantha; Pratt, Janey S.; Raghavan, Preeti; DeSilva, Jeremy M.
Abstract: Funding agencies and institutions are creating initiatives to encourage interdisciplinary research that can be more easily translated into community initiatives to enhance health. Therefore, the current research environment calls for interdisciplinary education and skills to create sustained partnerships with community institutions. However, formalized opportunities in both of these areas are limited for students embarking on research careers. The purpose of this paper is to underscore the historical and current importance of providing interdisciplinary training and community dissemination for research students. We also suggest an approach to begin to address the existing gap. Specifically, we suggest embedding a 10‐week summer rotation into existing research curricula with the goals of: (1) providing students with a hands‐on interdisciplinary research experience, (2) facilitating dialogue between research students and community settings to disseminate science to the public, and (3) sparking collaborations among researchers who seek to create a way to sustain summer program rotations with grant funding.